Revolutionary Traits in Wittgenstein and St. Paul A Comparative Study - Rono, Joseph (2018)
Philosophy experienced a turning point at the time of Ludwig Wittgenstein. Likewise, religion (Judaism) encountered transformation during the time of the apostle Paul. Wittgenstein’s metaphor of the "River-bed" that was later subsumed in the language-game theory is a concept that challenged the then status quo of philosophy known as rationalistic foundationalism. This philosophical predisposition is analogous to the religious situation when Paul began his Christian ministry. Paul’s passionate emphasis on "justification by faith" rather than legalistic or ritualistic observance of the law, was a shockwave to the Judaist religious establishment. Wittgenstein and Paul could as well be regarded as "radicals" or rebels in their respective disciplines. Wittgenstein introduced a paradigm shift into philosophy while Paul did it in the Christian religion. Their unconventional outlooks were, however, met with a lot of resistance especially from the diehard philosophers and/or religionists of the day. This paper, therefore, is a comparative work on Wittgenstein (Philosophy) and Paul (Religion) in order to demonstrate sustained revolutionary tendencies toward human innovations and the need to strive for excellence.